Development and evaluation of aceclofenac-loaded mucoadhesive microcapsules - Santhosh Kumar Mankala; Appanna Chowdary Korla; Sammaiah Gade (Wolters Kluwer Medknow Publications, 2011)
Microencapsulation is an accepted process used to achieve controlled release and drug targeting for many years. Mucoadhesion has been a topic of interest in the design of drug delivery systems to prolong its intestinal residence time. Mucoadhesion facilitates the intimate contact of the dosage form with the underlying absorption surface for improved bioavailability of drugs. Aceclofenac is a newer nonsteroidal anti-inflammatory drug (NSAID) having short biological half-life of 4-4.3 h, and therefore a sustained release medication is required to get prolonged effect and to reduce fluctuations in drug plasma concentration levels. Aceclofenac microcapsules were prepared employing sodium alginate as the coat material in combination with some mucoadhesive polymers such as (hydroxypropyl methyl cellulose) HPMC, (sodium carboxymethyl cellulose) Sod. CMC, Carbopol and methyl cellulose (MC) (drug:SA:polymer at ratios 2:2:1, 2:3:1 and 2:4:1), following orifice-ionic gelation technique. Infrared (IR) spectroscopy, differential scanning calorimetry and X-ray diffraction studies proved the compositions were compatible, without any interaction between the drug and excipients. The prepared microcapsules were evaluated for various physical and release parameters. The resulted microcapsules were found to be discrete and spherical in scanning electron microscopy studies and free flowing in rheological studies. The size of microcapsules was found to be around 757.44 ± 5.201 μm to 814.46 ± 6.586 μm. The microencapsulation efficiency was found to be higher in HPMC than in Carbopol > MC > Sod. CMC containing formulations, but the swelling index was found to be higher in Sod. CMC formulations. The microcapsules with HPMC exhibited good mucoadhesive property in the in vitro wash-off test. In vitro drug release studies of aceclofenac microcapsules were carried out up to 24 h and they followed zero-order release kinetics with Super Case II mechanism. The drug release from the microcapsules was sustained over a prolonged period with greater retardation in drug:SA:HPMC (2:4:1) containing microcapsules and this proved to be the best formulation.